DA FICÇÃO PARA A REALIDADE: RESISTÊNCIA À DITADURA MILITAR NA FRONTEIRA BRASIL-BOLÍVIA - Rodolfo César de Sousa (2024)
This paper analyzed how Antonio Callado’s literary work portrayed the Brazilian military dictatorship by delving into the microcosm of Brazil's border with Bolivia, between Corumbá and Puerto Suárez. The aim was to discuss the measures taken by a regime of excess that lasted 20 years and left scars on an entire country, even when that government decided to move in the direction of the democratic process, which was built in homeopathic doses and controlled by the military itself. Callado’s book Sempreviva was the guide for this critical reading and political and social contextualization. A bibliographical review based on a critical vision also found that this weighted democratic opening generated more lasting roots, which were anchored in the face of an action to erase memories through amnesty. Sempreviva's study involved correlating fictional facts that intersected with historical data and official documents that were confidential and secret during the dictatorship, but are now accessible to help us understand how the border and its population were monitored during the military regime. Based on qualitative work, with an interdisciplinary thread, the product of this investigation resulted in a discussion about the political and social scenario of the border during the Brazilian military dictatorship. It also addressed the context that transforms literature into a tool for reconstructing memory, which guarantees a voice and space for traumatic experiences and thus challenges the dominant narrative to pave the way for a counterpoint, "another story" to understand the past and better understand the present and what is not wanted for the future. This is why it can be conceptualized as contemporary romance containing denunciation of historical facts.